2009
DOI: 10.1080/02841850903059423
|View full text |Cite
|
Sign up to set email alerts
|

Imaging of gastrointestinal stromal tumors before and after imatinib mesylate therapy

Abstract: Gastrointestinal stromal tumors (GISTs) account for the majority of gastrointestinal mesenchymal tumors. Recent advances in treatment using the molecular targeting agent imatinib mesylate have shown startling response rates and variegated imaging findings. We present the various imaging appearances of GIST on computed tomography (CT) and magnetic resonance imaging (MRI), both before and after treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…However, it has been observed that RECIST can underestimate both responses to chemotherapy (alone or coupled with antiangiogenic agents) and focal therapies[8,11-13]. Indeed, solid tumors may respond to therapies by developing intratumoral necrotic areas and/or cystic or myxoid degeneration; as a result, the overall size of the neoplasm may be reduced, unchanged or paradoxically increased[12,14,15].…”
Section: Limitations Of the Conventional Qualitative Assessment Of Momentioning
confidence: 99%
“…However, it has been observed that RECIST can underestimate both responses to chemotherapy (alone or coupled with antiangiogenic agents) and focal therapies[8,11-13]. Indeed, solid tumors may respond to therapies by developing intratumoral necrotic areas and/or cystic or myxoid degeneration; as a result, the overall size of the neoplasm may be reduced, unchanged or paradoxically increased[12,14,15].…”
Section: Limitations Of the Conventional Qualitative Assessment Of Momentioning
confidence: 99%